Acquisition of extended spectrum β-lactamases during travel abroad—A qualitative study among Swedish travellers examining their knowledge, risk assessment, and behaviour. Issue 1 (1st January 2016) - Wiklund, Susanne; Fagerberg, Ingegerd; Örtqvist, Åke; Broliden, Kristina; Tammelin, Ann
Abstract : Background: Travel to foreign countries involves the risk of becoming a carrier of antibiotic-resistant bacteria, especially when the destination is a country with a high prevalence of this type of bacteria. Aim and methods: The aim of this study was to learn about the knowledge of antibiotic resistance, and the behaviour and risk-taking among travellers, who had become carriers of extended spectrum beta-lactamases (ESBL)-producing bacteria during travel to a high-prevalence country. A modified version of grounded theory was used to analyse 15 open interviews. Results: The analysis resulted in a core category: A need for knowledge to avoid risk-taking . Before the journey, the participants did not perceive there to be any risk of becoming a carrier of antibiotic- resistant bacteria. The low level of knowledge of antibiotic-resistant bacteria and transmission routes influenced their behaviour and risk-taking during their journey, resulting in them exposing themselves to risk situations. After their trip, the majority did not believe that their personal risk behaviour could have caused them to become carriers of ESBL. Conclusion: The participants' lack of knowledge of antibiotic-resistant bacteria resulted in unconscious risk-taking during their journey, which may have resulted in becoming carriers of ESBL-producing bacteria.